# How to prove this infinite series?

• B
• Imaxx

#### Imaxx

While transforming the equation of the Basel problem, the following infinite series was obtained.

$$\sum_{n=1}^{\infty} \frac{n^2+3n+1}{n^4+2n^3+n^2}=2$$

However I couldn't think of a simple way to prove that.
Can anyone prove that this equation holds true?

Your series can be put on the form of a telescope series and thereby summed up.
\begin{align*} \sum_{n=1}^\infty\frac{n^2+3n+1}{n^4+2n^3+n^2} &= \sum_{n=1}^\infty\frac{n^2+3n+1}{n^2(n+1)^2} \\ &= \lim_{N\rightarrow\infty}\sum_{n=1}^N\bigg\lbrace\frac{2n^2+3n}{(n+1)^2} - \frac{2(n-1)^2+3(n-1)}{n^2}\bigg\rbrace \\ &= \lim_{N\rightarrow\infty}\frac{2N^2+3N}{(N+1)^2} \\ &= 2, \end{align*}
where the last equality follows by successive use of l'Hopital's rule.

You don't need l'Hopital's rule here; just observe $$\frac{2N^2 + 3N}{(N + 1)^2} = \frac{N^2(2 + \frac 3N)}{N^2(1 + \frac1N)^2} = \frac{2 + \frac 3N}{(1 + \frac1N)^2}$$ and the result follows from the proposition that the limit of a ratio is the ratio of the limits provided the limit of the denominator is not zero.

This was a post in Calc & Beyond HW

I like to take the chance and remind you of our rules:
• 